Multi-omics integration identifies ganoderic acid A as a TNFα inhibitor for treating sepsis-related liver injury - Hu, Hong; Chen, Zike; Han, Jinlu; Chen, Mengyan; Song, Yun; Zhao, De; Wang, Chen; Shi, Min (Frontiers in Pharmacology, 2026)
Ganoderic acid A (GAA), a major bioactive triterpenoid from Ganoderma lucidum, is known for its anti-inflammatory effects; however, its precise molecular targets in sepsis-related liver injury (SRLI) remain unclear. Integrating network pharmacology and transcriptomic analysis, we identified Tumor Necrosis Factor-alpha (TNFα) as a primary candidate target. Subsequent biophysical validation using surface plasmon resonance (SPR) and molecular dynamics (MD) simulations confirmed that GAA directly binds to TNFα. Functionally, this interaction inhibits the TNFα/NF-κB signaling axis, thereby suppressing macrophage M1 polarization and ameliorating liver injury in vitro and in vivo. This study identifies TNFα as a primary candidate target of GAA, providing a mechanistic basis for its hepatoprotective effects and therapeutic potential.